2016
DOI: 10.1007/978-1-4939-6502-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling in Mitosis: An Updated View in Light of the MEN Pathway

Abstract: The Hippo pathway is an essential tumor suppressor signaling network that coordinates cell proliferation, death, and differentiation in higher eukaryotes. Intriguingly, the core components of the Hippo pathway are conserved from yeast to man, with the yeast analogs of mammalian MST1/2 (fly Hippo), MOB1 (fly Mats), LATS1/2 (fly Warts), and NDR1/2 (fly Tricornered) functioning as essential components of the mitotic exit network (MEN). Here, we update our previous summary of mitotic functions of Hippo core compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 96 publications
2
13
0
Order By: Relevance
“…In agreement with the role of Hippo in cell cycle progression and specifically in the mitotic phase, we found that several genes related to cytokinesis and mitotic spindle organization were differentially expressed in the hippo (RNAi) RNA sequencing analysis (RNAseq) ( S1 Table ). Importantly, these included genes already known to be regulated by Mst1/2 or Lats1/2 and mainly involved in spindle orientation ( afadin, Drosophila discs large, polo-like kinase 1 ) [ 38 40 ] ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the role of Hippo in cell cycle progression and specifically in the mitotic phase, we found that several genes related to cytokinesis and mitotic spindle organization were differentially expressed in the hippo (RNAi) RNA sequencing analysis (RNAseq) ( S1 Table ). Importantly, these included genes already known to be regulated by Mst1/2 or Lats1/2 and mainly involved in spindle orientation ( afadin, Drosophila discs large, polo-like kinase 1 ) [ 38 40 ] ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings demonstrate that in planarians, Hippo is essential for proper cell cycle progression and, specifically, for successful completion of mitosis. The role of core Hippo signaling elements in critical mitotic events, namely in centrosomal duplication, chromosomal alignment, spindle formation, and completion of cytokinesis, has also been reported in Drosophila and vertebrate species [ 36 , 40 , 50 53 ]. Planarian hippo (RNAi) cells showed improper assembly of the mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study [62] did not examine whether this molecular reprogramming of binding partners could be a possible consequence of cell cycle effects upon hMOB2 loss-of-function. Given that loss of hMOB2 can trigger a p53-dependent G1/S cell cycle arrest [37] and that NDR/LATS are associated with cell cycle progression [20,21], it will certainly be necessary to re-examine these HCC-based hMOB2 knockout cells to ensure the changes in NDR1/2, LATS1/2, and hMOB1 phosphorylation upon hMOB2 loss [62] are not merely reflecting indirect effects triggered by an underlying cell cycle arrest/delay.…”
Section: An Overview Of Mobs and The Hippo Pathwaymentioning
confidence: 99%
“…Since we are only briefly summarising here the mitotic functions of hMOB1, for a detailed overview of the cell cycle roles of hMOB1 see refs. [20,21]. Initially, a kinase-targeting RNAi screen found that the NDR1 kinase, a binding partner of hMOB1 and hMOB2 [1], is possibly involved in regulating spindle orientation [103].…”
Section: Cancer-associated Cellular Functions Of Mobsmentioning
confidence: 99%
“…We provide evidence for a NDR2/GEF-H1 interaction, leading to GEF-H1 Ser885 phosphorylation/inactivation, followed by RhoB down-regulation. Given the involvement of GEF-H1 and NDR kinases in cell cycle [10, 11], we investigated cell cycle alterations in RASSF1A-depleted HBEC. We found that RASSF1A knockdown induced mitotic abscission defects, which were reverted upon GEF-H1 overexpression or NDR1/2 depletion.…”
Section: Introductionmentioning
confidence: 99%